Pergulatan Pemikiran Melawan Arus: Penyempalan Dalam Tubuh Nahdlatul Ulama Dan Muhammadiyah - Mutawalli Mutawalli (Universitas Islam Negeri Mataram, 2007)
Political reform after the resign of the former president Suharto in 1998, open the channel of freedom of expression for the people of Indonesia. This enables the Muslims, as the majority of the Indonesian people to express their thoughts in any forms – either orally or in action. This condition resulted in the existence of the liberal progressive movement in Nahdlatul Ulama and Muhamadiyah. The intellectual critical attitude of the young generation in the Nahdlatul Ulama form some institutions such as Liberal Islamic Networks, Islamic Emancipators, Religious study and Democratic Institution, Islamic Study and Social Institution, Human Resource Development Institution; in Muhammadiyah, Muhammadiyah Youth Islamic Networks leads the thought reform. This phenomenon is a concept of dialectical process, communication, and expression of social reality—movements and thoughts are responses of the dialectical thought in the society. Liberal progressive thought appears to be contradictive, even.